Agresión Física y Psicológica estudio en el centro de educación básica “Nicanor Larrea” Riobamba Chimborazo período académico 2015-2016. - López López, Paola Yadira (2017)
The purpose of this research is to determine the type of aggressions that arise in the educational institution called “Nicanor Larrea” to investigate, the psychological consequences that can affect both their social and emotional existence throughout their lives, the important objective of this work is to identify the different causes of physical and psychological aggression with the purpose of analyzing the aggressive behavior of the students. Having used a non-experimental field documentary methodology, techniques and instruments that allowed the investigative process with a population of 78 students consisting of 25 women and 53 men, activities of creative characteristics, which facilitated the professor their execution. The observation sheet was used as an instrument to know who, due to physical and psychological aggression have difficulties in the educational institution, later the data were interpreted through statistical graphs with selected questions referring to the problem. It is observed that physical and psychological aggression directly affects the educational field. By knowing the problem, the teacher can prevent them from reaching the student emotionally, helping them to overcome them through dialogue, parents arc involved as a fundamental pillar of the family achieving excellent results in the student, raising their self-esteem and their relationship familiarizing the aggression both at home and at school improving the ability to relate and dialogue before reaching the blows between partners.